Para Perempuan, Kubur Kosong, dan Kebangkitan Yesus: Analisis Naratif terhadap Lukas 24:1-12 dan Penerapannya Masa Kini - Djuharto, Ivana Aimee (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2024)
This paper is intended to present a reading of Luke 24:1-12 using a narrative analysis approach and characterization theory in order to enrich research on related text. I combined narrative analysis method with Bennema’s characterization theory. This method explores narrative elements, such as: implied author and narrator; point of view and ideology; narration and time narration; plot; setting; characterization; and implied reader. Characterization of characters is done with the following step, such as: 1) Character analysis and classification, and 2) Total reconsturction of character. This writing specifically delves the narration inside the text of Luke 24:1-12 in accordance to elements mentioned above in order to provide the reader implications for living the live as a Christian nowadays. The result shows that the narrative analysis character reconstruction carried out in this text can enrich readers to understand Luke 24:1-12 as a whole narrative text. At the same time, this paper emphasizes that women who are not prominent characters can still be used by God to proclaim the gospel after God has processed them spiritually.